2019
DOI: 10.1021/acs.jpcb.9b07086
|View full text |Cite
|
Sign up to set email alerts
|

Energy Transport across Interfaces in Biomolecular Systems

Abstract: Energy transport during chemical reactions or following photoexcitation in systems of biological molecules is mediated by numerous interfaces that separate chemical groups and molecules. Describing and predicting energy transport has been complicated by the inhomogeneous environment through which it occurs, and general rules are still lacking. We discuss recent work on identification of networks for vibrational energy transport in biomolecules and their environment, with focus on the nature of energy transfer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 212 publications
(420 reference statements)
3
46
0
Order By: Relevance
“…We again found that, for non-bonded contacts interacting by short-range potentials, the energy transfer rate across the contact varies inversely with the variance in the contact length. A similar relation was found for the hydrogen-bonded contacts of the dimeric hemoglobin from Scapharca Inaequivalvis, HbI, in the unliganded state, including contacts with water molecules at the interface of the two globules (Leitner et al 2019;Reid et al 2020).…”
Section: Energy Exchange Network (Een) For Fixlsupporting
confidence: 69%
See 1 more Smart Citation
“…We again found that, for non-bonded contacts interacting by short-range potentials, the energy transfer rate across the contact varies inversely with the variance in the contact length. A similar relation was found for the hydrogen-bonded contacts of the dimeric hemoglobin from Scapharca Inaequivalvis, HbI, in the unliganded state, including contacts with water molecules at the interface of the two globules (Leitner et al 2019;Reid et al 2020).…”
Section: Energy Exchange Network (Een) For Fixlsupporting
confidence: 69%
“…The data plotted in green correspond to hydrogen bonding between interface water molecules and either lysine or arginine. Insets to (a) and (b) are schematic illustrations of the relation between fluctuations in the distance of a hydrogen bond and the rate of energy transfer between hydrogen-bonded residues, as quantified by the energy conductivity, G. Reprinted from (Leitner et al 2019), Copyright (2019), American Chemical Society state. When there is a change of state, we have seen with the example of FixL, as in earlier studies of PDZ (Ishikura et al 2015) and HbI (Gnanasekaran et al 2011;Leitner 2016), that the ΔEEN map identifies residues important in this process, indicating networks involved in allosteric transitions.…”
Section: Summary and Future Directionsmentioning
confidence: 99%
“…They also found pathways for energy transport via hydrogen bonds between residues distantly positioned in the sequence of the 35-residue villin headpiece subdomain (Buchenberg et al 2016;Leitner et al 2015). Recently, Leitner and coworkers discussed the rates of vibrational energy transfer for short-range polar contacts, such as hydrogen bonds, as well as at interface in biomolecules in the thermal equilibrium (Leitner et al 2019;Reid et al 2018). They mentioned that analyzing energy transfer across the van der Waals contact using molecular dynamics simulation is challenging because of the small energy conductivity.…”
Section: Mechanism Of Energy Flow In Proteinmentioning
confidence: 99%
“…Regarding this issue, Lervik et al [20] calculated the thermal conductivity at the protein-water interface in terms of classical molecular dynamics. Pandey and Leitner [21,22] quantum-mechanically evaluated the thermal energy transport through a trehalose layer between water and protein, and between gold, such as a gold nanoparticle, and its cellular environment.…”
Section: Introductionmentioning
confidence: 99%